PLEASE HELP ME I'M STUGGLING AND I NEED TO PASS FOR THE YEAR

Which of the following is in standard form of quadratic? f(x) = -3(x + 3)(x – 4) f(x) = -3(x - 2)^2 + 3 f(x) = -3x² – 3x + 2


Respuesta :

Answer:

f(x) = -3x² – 3x + 2

Step-by-step explanation:

Standard form of quadratic equation: [tex]f(x)=ax^2+bx+c[/tex]

Vertex form of quadratic equation: [tex]f(x)=a(x-h)^2+k[/tex]

(where (h, k) is the vertex of the function)

Intercept form of the quadratic equation:  [tex]f(x)=(ax+c)(bx+d)[/tex]

Therefore,

  • standard form:  [tex]f(x) = -3x^2- 3x + 2[/tex]
  • vertex form: [tex]f(x) = -3(x - 2)^2 + 3[/tex]
  • intercept form:  [tex]f(x) = -3(x + 3)(x -4)[/tex]